SISTEM INFORMASI PENJUALAN BARANG ELEKTRONIK PADA TOKO N2 (NEFA & NAILA) DI KEL. RANTAU BADAK: Systems, Information, Sales, Goods, Electronics, Visual Basic 6.0 - -, Nilawati (LP2M Universitas Nurdin Hamzah, 2019)
N2 Store (Nefa and Naila) Processing of sales and inventory data that has not been computerized raises several problems, including inaccurate inspection of existing items, frequent occurrence of goods disputes, search for the number of items and relatively long report-making process, errors in recording sales notes for example writing product name, price and quantity of goods. With the information system on selling goods at N2 Store (Nefa and Naila) computerized all previously conventional sales document data can now be stored properly. The benefits of this research are as input for N2 Store (Nefa & Naila) in Ex. Rantau Badak is expected with this new system to increase sales and progress for the store, both in the field of purchasing goods and selling goods to the consumers of N2 Store (Nefa and Naila) in Kel. Rantau Badak. The result of this research is an information system application for selling electronic goods at N2 store (Nefa and Naila) in Kel. Rantau Badak. With this application it can help Nefa and Naila store in the process of selling electronic products.